The first data from the Orion laser: measurements of the spectrum of hot dense aluminium. (March 2016) - Hoarty, D J; Allan, P; James, S F; Brown, C R D; Hobbs, L M R; Hill, M P; Harris, J W O; Morton, J; Brookes, M G; Shepherd, R; Dunn, J; Chen, H; et al.
Abstract: The newly commissioned Orion laser system has been used to study dense plasmas created by a combination of short pulse laser heating and compression by laser driven shocks. Thus the plasma density was systematically varied between 1 and 10g/cc by using aluminium samples buried in plastic foils or diamond sheets. The aluminium was heated to electron temperatures between 500eV and 700eV allowing the plasma conditions to be diagnosed by K- shell emission spectroscopy. The K-shell spectra show the effect of the ionization potential depression as a function of density via the delocalization of n=3 levels and disappearance of n=3 transitions in He-like and H-like aluminium. The data are compared to simulated spectra, which account for the change in the ionization potential by the commonly used Stewart and Pyatt prescription; a simple ion sphere model and an alternative due to Ecker and Kroll suggested by recent X-ray free-electron laser experiments. The experimental data are in reasonable agreement with the model of Stewart and Pyatt, but are in better agreement with a simple ion sphere model. The data indicate that the Ecker and Kröll model overestimates substantially the ionization potential depression in this regime.